Evaluation of Sulfuric Acid Application in Breaking Dormancy of Sida cordifolia Seeds - An Ayurvedic Medicinal Plant - HEMLATA BHARTI; P. MANIVEL; BIRENDRA KUMAR (Seed Research, 2026)
’Bala’ (Sida cordifolia L. Malvaceae) is an important ayurvedic medicinal plant used in the treatment of rheumatism, asthma, bronchitis, neuralgia, sexual debility etc. An experiment was conducted to evaluate the effect of different concentration and treatment duration of sulfuric acid on breaking the seed dormancy in Sida cordifolia, for optimizing its germination potential. The treatments included pretreatment of seeds with 50 and 100% sulfuric acid for 5, 15 and 25 minutes. The results showed that with the increase in the duration of treatment with sulfuric acid (50%), the seed germination percentage increased from 2% to 22% and radicle length and dry weight also increased from 3.543 to 6.067 cm and from 0.6 to 0.683mg, respectively. There was no significant difference among the treatments with sulfuric acid 100% for 5, 15 and 25 minutes.